Murine cells carrying integrated tandem genomes of hepatitis B virus DNA transcribe RNAs from endogenous promoters on both viral strands and express middle and major viral envelope proteins. - Zelent, A Z (1987)
Clone 4.10 cells were isolated as a methotrexate-resistant clone arising after cotransfection of mouse 3T3 cells with plasmid DNA containing a head-to-tail dimer of the hepatitis B virus (HBV) genome and DNA coding for methotrexate-resistant dihydrofolate reductase. The majority of methotrexate-resistant clones derived by this procedure have been found to contain multiple copies of the HBV genome, but the intact HBV dimer was rarely preserved. In contrast, 4.10 cells contained at least 40 copies of intact HBV dimer per cell. These cells produced large amounts of 22-nm hepatitis B surface antigen particles that included viral envelope proteins reactive with the pre-S2 region-specific antibody, indicating transcription and translation of the pre-S2 and S regions of the integrated viral genomes. The cells also synthesized viral e antigen, which was released into the culture medium. Characterization of polyadenylated viral RNAs transcribed from the long (minus) strand of the integrated HBV DNA demonstrated the presence of shorter-than-genome-length RNAs containing only X region sequences, shorter-than-genome-length RNAs containing both X and S region sequences, and longer-than-genome-length RNAs containing core, X, and S region sequences. Start sites for transcripts were mapped 5' to and within the pre-S region and 5' to and within the precore region at approximately the same sites as those utilized for HBV transcription during viral replication in infected livers. Polyadenylated RNA transcripts complementary to the short (plus) strand of HBV that initiated and terminated within the intact and integrated head-to-tail tandem viral genomes were also detected.